MENINGKATKAN HASIL BELAJAR IPS MELALUI PENERAPAN MODEL PEMBELAJARAN GROUP INVESTIGATION DI SMPN 1 BENAI - Erwandri (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article examines the improvement of students’ learning outcomes in social science by applying the Group Investigation (GI) learning model. GI is a cooperative learning method in which students actively participate in groups, express their opinions, and collaborate with peers. Learning outcomes are influenced by students’ understanding of concepts, goals, and motivation in relation to the learning material. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart spiral model, which consisted of planning, action, observation, and reflection in each cycle. The study involved 22 seventh-grade students of SMPN 1 Benai, comprising 8 male and 14 female students, conducted from April to May 2022. The initial test showed an average score of 59.09%. Cycle I results increased to 77.27%, categorized as medium, and Cycle II results reached 90.90%, categorized as very high. These findings indicate that the Group Investigation learning model effectively improves students’ learning outcomes.